Analysis of long-term observations of the large group of Russian patients with Hunter syndrome (mucopolysaccharidosis type II) - Alla Nikolaevna Semyachkina; Elena Yurievna Voskoboeva; Ekaterina Alexandrovna Nikolaeva; Ekaterina Yurievna Zakharova (BMC, 2021)
Abstract Background This article presents the results of long-term observations and comparative analysis of genotype-phenotype features in a large group of patients (227 males and one female) with a severe, intermediate and mild form of Hunter syndrome, evaluating the quality and span of their lives, as well as their ability to social adaptation. Methods We used electrophoresis of glycosaminoglycans of urine, determination of the activity of lysosomal enzymes in plasma, in dried blood spots according to the generally accepted method and DNA analysis. Results The clinical symptomatology of 228 patients with Hunter syndrome was characterized by growth retardation, lesions of the bronchopulmonary, cardiovascular, nervous systems, etc. Thirty-five patients had an attenuated form of the disease. DNA was available from all patients. 19 patients from 10 families had a mild form of the disease. 42 patients from 41 families had an intermediate form of the disease. All other patients had a severe form of the disease. We provide brief clinical examples of some patients with a mild form of Hunter syndrome. Currently, 113 patients with Hunter syndrome receive enzyme replacement therapy (idursulfase or idursulfase beta). Conclusion The long-term study of the large number of patients with Hunter syndrome helped identify disease-associated variants leading to severe and mild forms of the disease. The treatment effect and successful social adaptation of patients with a mild form of Hunter syndrome were revealed.